Integrating Protocol-driven Decision Support within E-Referral System: Supporting Primary Care Practitioners for Spinal Care Consultation and Triaging - Maghsoud-Lou, Ehsan (2014)
Referrals to the Halifax Infirmary Neurosurgery Department are submitted with regards to spinal conditions with different degrees of complications. Although there exists a Spinal Condition Consultation Protocol to standardize spinal referrals, the information provided from referring physicians is frequently inadequate to accurately triage the patient's condition, partly due to missing diagnostic therapies. The Neurosurgery Department receives a high volume of referrals each year, which imposes a significant administrative workload on the staff. We propose to develop a protocol-driven decision support system to: 1) Provide primary care physicians with timely access to condition specific consultation treatment protocols; and 2) Automate the referral assessment process to eliminate processing delays and administration burden. To this aim, we transformed the Consultation Protocol into a semantic knowledgebase. The decision support services are integrated within a standardized electronic referral system. We believe this system can significantly improve the referral process at the Neurosurgery Division.